Integer programming to optimize tamping in railway tracks as preventive maintenance - Cecília Vale (2012)
In the area with railway engineering, scheduling preventive maintenance actions is an important issue for engineers and railway administrations because the optimization of maintenance actions at a preventive level allows maintenance costs to be reduced during the life cycle of the track, with the guarantee of its geometrical quality. This paper describes a model designed to optimize the tamping operations in ballasted tracks as preventive maintenance. The model, formulated as mixed 0-1 linear program, considers real technical aspects as constraints, which is a novel approach in the optimization of track maintenance over time. Global optimization is used to predict and to schedule tamping, taking into account four aspects: the evolution of the track degradation over time; the track layout; the dependency of the track quality recovery on the track quality at the moment of the maintenance operation; the track quality limits that depend on the maximum permissible train speed. Computational experience with two track stretches of the Portuguese Northern Railway Line is included to highlight the efficacy of the proposed methodology. DOI:10.1061/(ASCE)TE.1943-5436.0000296. (C) 2012 American Society of Civil Engineers.